Dropping Out of the School: Factors and Its Impact On Primary School In Indonesia - Musa Masing; Kamsih Astuti (Psychosophia: Journal of Psychology, Religion, and Humanity, 2022)
The development of a nation's development is measured by the quality of human resources who have creativity, innovation, and measurable skills. One of the serious problems experienced by Indonesian Education at this time is the dropout problem. Various reasons for stopping school are still being considered, therefore this study seeks to describe in detail the factors and impacts of elementary school-aged children dropping out of school in Indonesia. The method used in this research is Systemic Literature Review. Data analysis was carried out on the content contained in the research objectives and research results. The analysis used is the analysis of the contents of the journal. The results of his research regarding the factors that cause school dropouts are Economic Factors, Cultural Factors, Family Factors, Family Education Factors, Environmental Social Factors, Interest and Intelligence Factors, School Factors. Meanwhile, the impact of dropping out of school for children of primary school age is a large number of unemployed, a large number of untrained workers, being the target of criminal groups, disturbing public security. The results of this study are expected to provide a reference for education practitioners in designing the right education system and pattern for elementary school-aged children.